THE ROLE OF INTERNAL AUDIT IN THE EVALUATION OF URBAN LOCAL GOVERNMENT EXPENDITURES (Polityki Europejskie, Finanse i Marketing)
The article presents the role and tasks of internal audit in the assessment of public expenditures in a selected area for municipal governments in Łódź, Piotrków Trybunalski and Skierniewice in Poland. The research found, among other things, that internal audits contribute to a more rational spending of funds from the city budget on public administration activities. In addition, it has also been shown that internal audit is a helpful tool in ensuring reasonable expenses for public finance sector entities. The assessment and monitoring of expenses is the responsibility of public authorities, to ensure rational financial management of a given local government unit. The aim of the article is to present internal audit as an important tool to support city authorities in assessing the expenditure of municipalities in a selected area. For the purposes of this publication, local government units from the Łódź Voivodeship, i.e. a city with district status, were selected as an example for analysis. In this article, case study, analytical method, inference method and document examination method were used as research methods. To make the necessary analyses, materials made available by the surveyed entities and data available in public registers collected by authorized institutions were used.